Poverty prevalence and correlates of household expenditure in four lowland areas of rural Papua New Guinea - Schmidt, Emily; Gilbert, Rachel; Holtemeyer, Brian; Mahrt, Kristi (International Food Policy Research Institute, 2019)
The lack of data on rural household production systems and economic conditions in Papua New Guinea (PNG) has impeded efforts to inform development initiatives for the last decade. In 2015/16, a severe El Niño event decimated local crop production and underscored the lack of current data and analysis of PNG’s rural population. This paper presents recently collected data from a rural household survey in PNG, including detailed consumption and expenditure data, to explore poverty prevalence and vulnerability in selected rural areas. In doing so, we evaluate food production and consumption patterns within the survey areas and calculate area-specific poverty lines. In addition, we explore correlates of household consumption expenditure. Results suggest that approximately half of the survey sample have total consumption expenditure below the poverty line. When evaluating calorie consumption by food groups, we find that the rural diet is heavily dependent on starchy foods and a large share of the sample has insufficient protein intake per capita. Further evaluation of the correlates of household expenditure suggest four potential policy initiatives to explore further as conduits to improving overall welfare: 1) identify measures to increase agricultural production and improve resilience to climate shocks; 2) increase investments in education; 3) seek opportunities to enhance migration out of rural areas and 4) reduce the number of household dependents. Given that approximately 80 percent of the population in PNG is dependent on rain-fed, subsistence agriculture, rural data collection and analysis to inform policy priorities and development investments are critical to ensure economic viability and food security. This paper presents the most recent poverty analysis in PNG in nearly a decade and a renewed effort to better inform development priorities for the country’s rural population.